The break with tradition (Center for Humanities seminars in modern art, 1986)
Introduces the origins of modern art with the revolt of the impressionists against academic realism in the late 19th century. Details the reaction against pure impressionism in the 1880's with a commentary on such artists as Claude Monet, Camille Pissarro, Auguste Renoir, Edgar Degas, and Mary Cassatt.